2023
DOI: 10.3390/agronomy13020369
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Aeration and Root Morphology on Yield under Aerated Irrigation

Abstract: Soil compaction easily causes root hypoxia stress, resulting in poor root growth and the absorption of soil water and nutrients. We hypothesized that aerated irrigation (AI) could enhance nutrient uptake and utilization, thus unlocking the high yield potential by increasing soil aeration and root morphology indicators compared with that in the non-aeration treatment. A greenhouse experiment was conducted to investigate the effect of soil aeration and root morphology on the yield of greenhouse cucumbers. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…This effect was greater when the gas used was oxygen. Similar results have been obtained by Jin et al [5] in pumpkins with aerated irrigation, or by Wang et al [20], who found that oxygenation significantly promoted root development, mainly in the form of longer root length and increased root surface area.…”
Section: Root Length Density and Petiole Sapsupporting
confidence: 89%
See 1 more Smart Citation
“…This effect was greater when the gas used was oxygen. Similar results have been obtained by Jin et al [5] in pumpkins with aerated irrigation, or by Wang et al [20], who found that oxygenation significantly promoted root development, mainly in the form of longer root length and increased root surface area.…”
Section: Root Length Density and Petiole Sapsupporting
confidence: 89%
“…Oxygen availability is considered one of the most important factors for plant growth, after water and nutrient availability [1]. Low oxygen and high CO 2 concentrations, such as those that may occur in certain intensive irrigation systems, especially in heavy soils, negatively affect plant growth and productivity [2][3][4] and may affect the architecture and distribution of the root system [5,6]. In recent decades, many active techniques for soil or substrate aeration have been introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Good soil aeration is crucial for root differentiation and growth. Roots differentiate easily in well-aerated soil; whereas in poorly aerated soils, excessive CO 2 can be toxic to the root system, hindering growth [ 21 ]. Our results indicate that the soil CO 2 content was significantly higher in the drip irrigation treatments than under hole irrigation within the first month after transplanting.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, poor soil aeration leads to hypoxia, reducing transpiration, nutrient uptake, and overall plant growth. Effective soil aeration enhances redoxase enzyme activity and root metabolism, improving nutrient absorption and accelerating plant growth and yield [59]. In drip irrigation with plastic film mulch without soil submergence, variations in soil aeration due to irrigation and mulching practices influence nutrient availability due to aerobic microorganisms and nitrogen use efficiency, resulting in overall plant growth and yield.…”
Section: Discussionmentioning
confidence: 99%